INFLUENCE OF WEATHER FACTORS ON INCIDENCE OF SHOOT AND FRUIT BORER (Earias vittella Fabiricus) ON BHENDI - S. SATHYA, K. ARCHUNAN, M. PAZHANISAMY, (Horticultural Biotechnology Research)
The field experiments were carried out in the farmer field at C. Mutlur near Chidambaram during rabi and kharif 2017. The results of experiments revealed that the per cent shoot damage and fruit damage by E. vittella on bhendi reached peak on 13th and 15th MSW in rabi season, whereas 43rd and 42nd MSW in kharif season. The per cent shoot damage and fruit damage by E. vittella were exerted significantly positively correlated with minimum (0.552 & 0.698) and maximum temperature (0.629 & 0.748), whereas rainfall positively correlated with per cent shoot and fruit damage but it was non significant (0.111 & 0.297), however relative humidity (-0.178 & -0.210) and sunshine hours were exerted negatively correlated with per cent shoot damage and fruit damage by E. vittella during rabi 2017. The kharif season 2017 indicated that per cent shoot damage and fruit damage of bhendi was positively non significant association with RH and rain fall, while negatively non significant correlation with minimum temperature (-0.43 & -0.309) and sunshine hours (-0.265 & -0.283) was recorded.